Dynamic Content Analysis: Psychological Main Actor in the Film "Ku Kira Kau Rumah" Via Structure Three Acts - Moh Kholid; Mochammad Abdul Ghofur; Asfira Rachmad Rinata; Latif Fianto (Cakra Communico: Journal of Communication Science, 2024)
Film is one of the media communication mass To use convey message to viewer . The messages conveyed give meaning and power pull separately . Films with the drama genre are one of them most types of films interested by a number of people circles . There are many drama genres interested Because the story there is in the film use approach to reality social. The film "Ku Kira Kau Rumah " is one of the popular films in Indonesia with the drama genre. Issues raised​ in this film about mental health . This movie give description about survivor deep bipolar disorder undergo his life . This matter interesting attention For Then researched about change behavior or dynamics psychology that happens to the characters cast main in the film. So that can know How condition psychological can change behavior someone . Study This use method qualitative descriptive with analysis fill in and through approach psychoanalysis . Result of study This show that in the film "Ku Kira Kau Rumah " there is a number of change psychological can​ concluded as change emotions are not stable , too sensitive in respond environment and depression face family and friends near . The hope Hopefully study This can give addition knowledge about bipolar disorder and for study furthermore can more details and can see from more perspective​ wide.